Multiple myeloma—dynamic developments regarding disease understanding and therapy Multiples Myelom – dynamische Entwicklungen in Krankheitsverständnis und Therapie - Steinbrunn, Torsten; Knop, Stefan; Einsele, Hermann (Onkologe, 2020)
Multiple myeloma is a clonal plasma cell malignancy which is primarily located in the bone marrow and leads to the suppression of the normal hematopoiesis. The entity has its highest incidence in the elderly. Advances in molecular genetic diagnostics have significantly broadened the understanding of the disease’s underlying biology. Stepwise introduction of novel drugs such as proteasome inhibitors, immunomodulatory drugs and monoclonal antibodies as well as the use of effective combination therapies have markedly improved the prognosis of patients including those with multiple prior lines of therapy. However, cure is still not possible. Novel therapeutic strategies primarily using immunological and targeted approaches will enrich future treatment options and further improve survival for those affected by multiple myeloma.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Antibodies; monoclonal; Immunomodulation; Immunotherapy; Proteasome inhibitors; Stem cell transplantation; autologous